Botswana : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper and Statistical Appendix provides medium-term estimates of the cost of the government's current anti-HTV/AIDS policies and programs in Botswana. The paper throws light on the policy challenges that Botswana authorities face in combating the crisis. The findings suggest that the cost of treating HIV/AIDS patients is likely to be high, about 10 percent of GDP, by 2010 (using the baseline estimates). The paper also analyzes Botswana's approach to medium-term fiscal management.